Input-specific excitation of olfactory cortex microcircuits - Luna, Victor M.; Morozov, Alexei (Frontiers in Neural Circuits, 2012)
Every higher-order association cortex receives a variety of synaptic signals from different regions of the brain. How these cortical networks are capable of differentially responding to these various extrinsic synaptic inputs remains unclear. To address this issue, we studied how the basolateral amygdala (BLA) and the anterior piriform cortex (aPC) were functionally connected to the association olfactory cortex, the posterior piriform cortex (pPC). We infected the BLA and aPC with adeno-associated virus expressing channelrhodopsin-2-Venus fusion protein (ChR2-AAV) and recorded the excitatory postsynaptic currents (EPSC) resulting from photostimulation of either BLA or aPC axons in the major classes of excitatory and inhibitory neurons of the pPC. We found that BLA and aPC axons evoked monosynaptic EPSCs in every type of pPC neuron, but each fiber system preferentially targeted one excitatory and one inhibitory neuronal subtype. BLA fibers were most strongly connected to deep pyramidal cells (DP) and fast-spiking interneurons (FS), while aPC axons formed the strongest synaptic connections with DPs and irregular-spiking interneurons (IR). Overall, our findings show that the pPC differentially responds to amygdaloid versus cortical inputs by utilizing distinct local microcircuits, each defined by one predominant interneuronal subtype: FS for the BLA and IR for the aPC. It would thus seem that preferential excitation of a single neuronal class could be sufficient for the pPC to generate unique electrophysiological outputs in response to divergent synaptic input sources.